How to decide between buying or renovating agricultural tractors? - Vidal, Diego Onofre [UNESP]; da Silva, Rouverson Pereira [UNESP]; de Oliveira, Bruno Rocca [UNESP]; Conceição, Elimar Veloso; Santos, David Ferreira Lopes [UNESP] (My University, 2022)
Deciding whether to buy or rebuild a tractor and when to do so is an empirical problem for farmers and/or rural administrators, whose analytical methods explored in the literature do not provide a clear approach to the operational and economic effects in the short and long term, despite its importance to the competitiveness of the activity. If the cost of replacing the agricultural tractors used in spraying the citrus crop could be more helpful than the reform of these, this study aimed to build and validate an economic evaluation method to support the decision to buy new or replace existing wheel tractors. To achieve such goals, a database with quarterly operational and financial information on 47 tractors between 2009 and 2017 was constructed. The method combined the use of an empirical, with the use of model panel-data regression, combining cross-sectional data with time series, to establish the actual cost information to be used in the model, and finally, implement the discounted cash flow, in which all uncertainties were controlled using a Monte Carlo simulation. The results indicated that the best decision is to purchase new equipment only after the fourth year of use. It stands out in the study findings, the impact of tax benefits and the resale of tractors were relevant to the cash flow, as well as the increase in maintenance costs over time. The economic evaluation method applied in this study can help rural producers and administrators in the decision-making process for investments in fixed assets and innovative technologies, thereby enabling them to be more accurate in their investment decisions. Technological progress increases the obsolescence rate of agricultural machinery and equipment whose paradigm referring to replacement was restricted to costs and operating conditions. In this study, it was found that the aggregate impact of expenditures and tax benefits had significant relevance on cash flow, therefore, should guide the analysis to create economic value.
Keywords: Agricultural machinery; Investment decisions; Valuation